The mitigation of carbon deposition for Ni-based catalyst in CO2 reforming of methane: A combined experimental and DFT study - Wuji lai; Lin Wang; Zhongde Dai; Lu Yao; Lin Yang; Wenju Jiang (Carbon Capture Science & Technology)
The dry reforming of CH4 (DRM) reaction can simultaneously convert two greenhouse gases CO2 and CH4 into high valued syngas. Nickel-based catalysts have been widely studied because of the low cost and high activity. However, carbon deposition making the deactivation of Ni-based catalyst is the main challenges for DRM reaction. This review illustrates DRM reaction mechanism and the causes of carbon deposition, as well as the resistance strategies of carbon deposition for Ni-based catalyst. The deposited carbon can be restrained by adjusting the size of Ni particles, introduction of promoters, reasonable design of support, controlling the reaction process and employing the confinement effect of the catalysts. The valuable insights are garnered for the further augmentation and optimization of the anti-carbon performance of catalysts by DFT and microkinetic. This work provides a tutorial for designing Ni-based catalysts with high anti-carbon deposition properties for DRM reaction.